ChemInform Abstract: Cinchona Alkaloids Induce Asymmetry in the Insertion Reaction of Thermally Generated Carbenes into N—H Bonds. Issue 13 (18th March 2013) - Saito, Hiroaki; Morita, Daisuke; Uchiyama, Taketo; Miyake, Muneharu; Miyairi, Shinichi
Abstract Among some derivatives tested, best results are obtained with dihydrocinchonine as a moderately efficient catalyst to produce phenylglycines.